MYC drives group 3 medulloblastoma through transformation of Sox2+ astrocyte progenitor cells - Tao, Ran; Okonechnikov, Konstantin; Kool, Marcel (Cancer research, 2019)
A subset of group 3 medulloblastoma frequently harbors amplification or overexpression of MYC lacking additional focal aberrations, yet it remains unclear whether MYC overexpression alone can induce tumorigenesis and which cells give rise to these tumors. Here, we showed that astrocyte progenitors in the early postnatal cerebellum were susceptible to transformation by MYC. The resulting tumors specifically resembled human group 3 medulloblastoma based on histology and gene-expression profiling. Gene-expression analysis of MYC-driven medulloblastoma cells revealed altered glucose metabolic pathways with marked overexpression of lactate dehydrogenase A (LDHA). LDHA abundance correlated positively with MYC expression and was associated with poor prognosis in human group 3 medulloblastoma. Inhibition of LDHA significantly reduced growth of both mouse and human MYC-driven tumors but had little effect on normal cerebellar cells or SHH-associated medulloblastoma. By generating a new mouse model, we demonstrated for the first time that astrocyte progenitors can be transformed by MYC and serve as the cells of origin for group 3 medulloblastoma. Moreover, we identified LDHA as a novel, specific therapeutic target for this devastating disease. - Significance: Insights from a new model identified LDHA as a novel target for group 3 medulloblastoma, paving the way for the development of effective therapies against this disease.
Gesehen am 16.05.2019
Im Titel ist das + in Sox2+ hochgestellt